1994
DOI: 10.1002/jlac.199419940110
|View full text |Cite
|
Sign up to set email alerts
|

Beschleunigung von Substitutionsreaktionen eines Phosphorsäurediesters durch Bis(guanidinium)‐Verbindungen

Abstract: Acceleration of Substitution Reactions of a Phosphoric Acid Diester by Bis(guanidinium) CompoundsIon-pair coordination of phosphoric acid diesters with positively charged guanidines may cause large rate accelerations in substitution reactions. Here we present a comparative study on the catalytical influence of several mono-bis-and tris(guanidines) and of other cationic compounds. Large rate effects occur if 1,3-bis(aminomethyl)benzene or 1,2-ethy-RNA cleaving agents. lenediamine are used as spacers. Further ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 56 publications
2
24
0
1
Order By: Relevance
“…3; Fig. 2): in dipolar aprotic solvents nucleophilic substitutions of a model phosphodiester are accelerated by factors up to 4800 [62] [63]. Similar results have been obtained by other scientists [59] [64] [65].…”
supporting
confidence: 86%
“…3; Fig. 2): in dipolar aprotic solvents nucleophilic substitutions of a model phosphodiester are accelerated by factors up to 4800 [62] [63]. Similar results have been obtained by other scientists [59] [64] [65].…”
supporting
confidence: 86%
“…Our strategy for the formation of 8 (X ϭ O) and 8 (X ϭ S) is similar to that reported by Lehn et al, [38] which focused on the addition of amines and isothiocyanates, and that reported by Göbel et al, [29] in which a thiourea unit bearing two terminal amines reacts with a diisothiocyanate in the final macrocyclization step. Treatment of a twofold excess of diamine 2 with Boc anhydride, with use of a continuous extraction method for product isolation, gave a mixture of 97% monoprotected 3 and 3% diprotected diamine 4.…”
Section: Synthesissupporting
confidence: 51%
“…Density functional theory (DFT) calculations (at the B3LYP/6-31G* level of theory) on the macrocycles with X ϭ S and O and with C 3 symmetry (the highest point group in which all macrocycles are minima) predict a cavity size of 2.727 Å for X ϭ O and 2.922 Å for X ϭ S. Interestingly, the macrocycles with X ϭ NH and X ϭ CH 2 or CH, such as Göbels macrocycle 19 [29] (the size of which is between that of the O-and that of S-macrocycle) can be ruled out as potential receptors, because the hydrogen atoms in the spacer group X would sterically interfere with a bound nitrate and with the thiourea NϪH groups. This leaves the macrocycles with X ϭ O and S as possible candidates for synthesis.…”
Section: Design Of the Receptor Structurementioning
confidence: 99%
See 1 more Smart Citation
“…They generally consist of oligo amines [4], guanidines, or structurally analogous heterocycles [2] [3]. In recent years, we have studied the catalysis of phosphoryl-transfer reactions by guanidinium salts {3-[(guanidino)methyl]phenyl}methylguanidine (1b) and 2-[(3-{[(4,5-dihydro-1H-imidazol-2-yl)amino]methyl}phenyl)methyl]amino-4,5-dihydro-1H-imidazole (2b) [5] [6]. With highly reactive model substrates in dipolar aprotic solvents, large rate increases could be observed.…”
mentioning
confidence: 99%